An effectively protective VLP vaccine candidate for both genotypes of feline calicivirus - Yang, Yupeng; Liu, Zhe; Chen, Mengru; Feng, Kexin; Qi, Ruibin; Kang, Hongtao; Jiang, Qian; Qu, Liandong; Liu, Jiasen (Frontiers in Immunology, 2024)
Feline calicivirus (FCV) is one of the most widespread pathogens affecting feline animals. Currently, FCV is believed to be divisible into two genotypes, with prevalent strains encompassing both GI and GII. Vaccination is the primary means of preventing FCV infection, yet traditional inactivated or attenuated vaccines theoretically pose potential safety concerns. In this study, a virus-like particles (VLPs), named DL39-VLPs, was constructed, using the VP1 gene of FCV DL39 strain with broad neutralizing and protective properties as a template through insect cell expression system. Cats were immunized with a 50 μg dose of DL39-VLPs mixed with an oily adjuvant via subcutaneous injection in the neck. For feline antisera positive for DL39-VLPs, the titer range in neutralization tests against prevalent GI strains ranged from 1:151 to 1:538, whereas the titer range in neutralization tests against prevalent GII strains was between 1:65 and 1:113. Challenge trials demonstrated that cats immunized with DL39-VLPs exhibited no significant clinical symptoms and had significantly reduced viral shedding and viremia compared to the challenged control group. Ultimately, a safe and highly protective VLP vaccine candidate, DL39-VLPs, was developed, which provides an important tool for the prevention and control of FCV infection.